Molecular dynamics studies of interfacial crystallization behaviors in polyethylene/carbon nanotube composites. Issue 124 (27th November 2015) - Yu, Bowen; Fu, Sirui; Wu, Zhiqiang; Bai, Hongwei; Ning, Nanying; Fu, Qiang
Abstract : The interfacial crystallization of polyethylene can be greatly affected by the SWCNT surface topography and pre-orientation of the polyethylene chains. Abstract : Molecular dynamics simulations were utilized to study the interfacial crystallization between polyethylene (PE) and single walled carbon nanotubes (SWCNTs). The early stages of PE crystallizing on the surface of SWCNTs and a SWCNT bundle were studied for comparison. The result showed that the PE chain tended to stabilize in the grooves of the SWCNT bundle and extended along the direction of SWCNTs afterwards. The early arrived chain could then lead to a regular arrangement of other chains and this was conducive to the formation of interfacial crystallization. Also, the inner mechanism of interfacial crystallization in solution and melt had been investigated. It was found that in solution, the interfacial crystallization of PE is a spontaneous process. However, in melt the interfacial crystallization strongly depended on the pre-orientation of the PE chains. This will help to understand the origin of polymer interfacial crystallization and guide the fabrication of high performance polymer/CNT nanocomposites via interfacial crystallization.